The metapleural glands of fungus-growing and non-fungus-growing ants: Ultrastructural study - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Brill Academic Publishers, 2014)
The metapleural glands are considered an autapomorphic structure to ants and probable have an antibiotic or antifungal function. The present study was aimed at investigating the ultrastructural morphology of the metapleural glands in ants which have different feeding types: from fungus-growing ants, the higher and lower attine, and non-fungus-growing ants from the tribes Blepharidattini and Ectatommini analyzed by transmission electron microscopy. Plasma membrane invaginations in secretory cells of both fungus-growing and non-fungus-growing ants facilitate absorption of extracellular material from hemolymph. Higher and lower attines differed slightly from non-fungus-growing ants, by the presence of oval secretory cells and well-developed RER in the metapleural glands, which indicates a higher production of secretion in attines. Also, well-developed Golgi regions in the leaf-cutting ants and Ectatommini probably modify the secretions, produced by the secretory cell or coming of the hemolymph, into pheromone or antimicrobial compounds, the latter mainly in leaf-cutting ants. Still, the secretory cells of the metapleural gland of leaf-cutting ants exhibited several mitochondria near microvilli of the intracytoplasmic portion of the canaliculus, indicating an important role of the metapleural gland in the production and transport of secretion in metapleural gland of leaf-cutting ants. Thus, our work corroborates other findings, however our results add that the slight ultrastructural difference in the metapleural glands of leaf-cutting ants can be due to the feeding type (fungus-growing ants), resulting in greater secretory capacity and antimicrobial properties to combat pathogens (for example, micro-fungi parasites Escovopsis).
Keywords: Exocrine gland; leaf-cutting ants; organelles; secretory cell